Lumea romanului românesc (1965–1989). Locuri şi timpuri - Ioana Revnic (Revista de Istorie și Teorie Literară)
A foray into the Romanian novel world between 1965 and 1989 is a journey through a literary geography that includes: First, the local village, either depicted through its traditional stance or disturbed by unexplained events; or under the renewing swing because of the negative influence of the collectivization and modernization. Secondly, the village over the Prut River – an invaded territory. Subject to the aggression of some forces from abroad – manifested during the war or during the communist occupation – the rural space remains the favorite background for the Bassarabian authors. Besides these places, there are the provincial cities (fatally marked by mediocrity), the imaginary provinces, and Bucharest. The capital is the sum of contrasts – a mix of old and new, of traditionalism and modernity, of elegance and kitsch. The town’s charm fades with time. Bucharest is so much transformed that the fictional depictions of the spectacular inter-war town seem to have nothing to do with the miserable city of the ’70–’80.